Interhemispheric water exchange in the Atlantic Ocean - Goni, G. J.; Malanotte-Rizzoli, Paola, 1946-; ScienceDirect eBooks (Amsterdam ; San Diego, CA : Elsevier, 2003)
Recent results from modeling and observational studies demonstrate that the tropical Atlantic is a critical region for processes that maintain the meridional overturning circulation, such as cross-equatorial exchanges, and for sea surface temperature variability that impacts on climate variability of the coupled tropical ocean/atmosphere system. The theme of this book is the inter-hemispheric and inter-gyre exchanges of heat, salt and fresh water, while its goal is to improve the knowledge of the tropical Atlantic dynamics and how it affects the global ocean.
Circulation, variability and near-equatorial meridional flow in the central tropical Atlantic -- Comparison of hydrographic and altimeter based estimates of sea level height variability in the Atlantic Ocean -- Estimation of the tropical Atlantic circulation from altimetry data using a reduced-rank stationary Kalman filter -- A synthetic float analysis of upper-limb meridional overturning circulation interior ocean pathways in the tropical/subtropical Atlantic -- A seasonal and interannual study of the western equatorial Atlantic upper thermocline circulation variability -- Fate of the equatorial undercurrent in the Atlantic -- The flow of AAIW along the equator -- Planetary equatorial trapped waves in the Atlantic ocean from TOPEX/POSEIDON altimeetry -- Pathways and variability at intermediate depths in the tropical Atlantic -- A comparison of kinematic evidence for tropical cells in the Atlantic and Pacific oceans -- Subtropical cells in the Atlantic ocean: An observational summary -- Spectral, formal, and nonlinear stability in a layered quasigeostrophic model with application to the Atlantic North Equatorial current -- Shynoptic study of warm rings in the North Brazil Current retroflection region using satellite altimetry -- North Brazil Current rings and the variability in the latitude of retroflection -- North Brazil Current rings and transport of southern waters in a high resolution numerical simulation of the North Atlantic -- Cross-gyre transport by North Brazil Current rings -- Impact of North Brazil Current rings on local circulation and coral reef fish recruitment to Barbados, West Indies -- Wind bursts and enhances evaporation in the tropical and subtropical Atlantic ocean -- Spatial-temporal evolution of the low frequency climate variability in the tropical Atlantic.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Ocean circulation -- Atlantic Ocean; Ocean-atmosphere interaction -- Atlantic Ocean; SCIENCE -- Earth Sciences -- Oceanography; NATURE -- Ecosystems & Habitats -- Oceans & Seas; Ocean-atmosphere interaction; Ocean circulation; Atlantic Ocean; Electronic books